Co-circulation of Flanders Virus and West Nile Virus in Culex Mosquitoes (Diptera: Culicidae) from Chicago, Illinois. Issue 4 (12th April 2018) - Poh, Karen C; Martin, Estelle; Walker, Edward D; Kitron, Uriel; Ruiz, Marilyn O; Goldberg, Tony L; Hamer, Gabriel L
Abstract: West Nile virus (WNV) and Flanders virus (FLAV) co-occur in regions of North America. Because both viruses are maintained in a transmission cycle involving Culex mosquitoes and birds, screening mosquitoes for FLAV has been suggested as an enhancement to WNV surveillance and epidemic prediction. Using samples collected in 2010 and 2012 in Chicago, IL, USA, we demonstrate the presence of FLAV in four out of 287 (1.4%) Culex pools. We estimated minimum infection rates for WNV and FLAV to be 5.66 and 1.22 in 2010 and 8.74 and 0.61 in 2012, respectively. FLAV occurred 1 and 3 wk prior to the peak of WNV transmission in 2010 and 2012, respectively. FLAV sequences from Chicago were genetically diverse and phylogenetically representative of lineage A viruses from across the United States.